Como incide la metodología de los docentes de cultura física en el proceso enseñanza aprendizaje en la disciplina de fútbol en los colegios mixtos nacionales de la ciudad de Loja, en los octavos años de educación básica en el año académico 2012-2013 - Aguirre Matailo, Edwin Enrique (2014)
In the present investigation was determined as incident Methodology of Physical Education Teachers in Teaching Learning Process in students through skills and cognitive skills. The investigation meet the overall objective is to determine the impact has the use of Teaching Learning Process of Physical Culture in students the basic cycle in the "Adolfo Valarezo" National College of the City of Loja in the period 2012-2013 ; and specific objectives such as: analyzing whether teaching and learning processes used by teachers in the area of Physical Culture, facilitate the achievement of significant learning in students; likewise to know the Methodology The Teaching Learning Process in Physical Education teachers, if limited or no significant learning in students; and determine if results come using teachers of Physical Culture, to identify the limitations and strengths of the Methodology of Physical Culture in the students the basic cycle in the "Adolfo Valarezo" National College The techniques used was the survey of teachers of Physical Culture and interviews with the students, more than the observation guide the teaching-learning process of Physical Culture, results that allowed to make findings and recommendations to improve and strengthen the use of methodological strategies that generate learning significant in students. The population surveyed was 6 teachers and 79 students, it was necessary to use the scientific method, synthetic and analytical hypothetical deductive method through descriptive procedure As a general conclusion of this work it was determined that the use of the methods are suitable by the teachers of the Department of Physical Culture, do not affect training in achieving meaningful learning. In the students' Adolfo Valarezo "National College.